Pattern and outcome of childhood intestinal obstruction at a Tertiary Hospital in Nigeria (2009)
Background: Intestinal obstruction is a common cause of pediatric surgical emergency with a high morbidity and mortality in Africa. Methods: A retrospective review of cases managed from January 1996 to December 2005 at a teaching hospital in Southwestern, Nigeria was done to examine the pattern of causes of intestinal obstruction in children and the management outcome. Results: One hundred and thirty cases were seen over the study period with an age range of 2 hours to 14 years. Majority (61.24%) were infants, while 18.46% were neonates. Fifty-five cases (42.31%) were due to congenital causes while the rest were of acquired causes. The major causes of intestinal obstruction in the study were intussusception (29.23%), anorectal malformations (22.31%), obstructed inguinoscrotal hernia (16.92%) and Hirschsprungís disease (13.85%). Surgical site infection and sepsis were the commonest complications observed with an overall complication rate of 60.78%. The mortality rate was 3.08% and most (75%) occurred in neonates. Conclusion: While mortality as an outcome of management is low, the morbidity was very high in this study.